Accidental findings of maxillary sinuses in dental patients on CBCT images. A retrospective study - Fedil Andraws Yalda (Erbil Dental Journal)
Background and objective: Maxillary sinus pathology is a common finding on routine CBCT scans of the maxilla. Hence the objective of this study is to define the frequency of accidental findings within maxillary sinuses on patients’ CBCT images that are referred for various dento-alveolar reasons in the maxilla and to evaluate the relation of the age and gender with the maxillary sinus condition. Methods: A total of 255 sequential CBCT scans from patients aged between 15-78 years, with a localized field of view (8.0cm x 5.0 cm) were retrospectively included in the analysis, resulting in an evaluation of 510 maxillary sinuses. The findings were categorized as healthy sinus, mucosal thickening, polypoid thickening and partial opacification. Result: Out of 255 patients, 148 (58%) were males and 107 (42%) were females with a mean age of 50.23 (SD=19.08). Implant assessment was the major request 206 (80.8%) followed by exploration of impacted teeth 35 (13.7%). 52.2% of included cases showed sinuses with no pathology (NP). 47.8% showed accidental findings of wich mucosal thickening (MT) was the highest 104 (40.8%). The relationship between gender and maxillary sinus status was statistically non-significant (p=0.346). The relation of the age (≤50 and >50) and sinus status, however, was statistically significant (p=0.035)